Optimization of growth rate and feeding efficiency of four economically important in the bioflocs system - HANAFIE, AGUSSYARIF; MURJANI, AKHMAD; REDHA, EL (Jurnal Natural, 2025)
Abstract. Research and development of biofloc aquaculture system until now only in the range of 14-15 species conducted. Even though this technology is able to increase production several times compared to conventional systems, so it is necessary to diversify species that allow development, especially economically important fish. There are 4 species of fish that are feasible to be developed, especially freshwater fish groups in wetlands, such as fish (climbing perch; Anabas testudineus Bloch, snakehead, Channa striata Bloch, giant gouramy , Opronemus gouramy and Pangas , Pangasius hypophthalmus. This research has been carried out in the range of June 2023- February 2024 using a complete randomised complete block design, 4 treatments climbing perch; snakehead, giant gouramy and pangas with 4 replicates. Stocking density of 1000 fish 2500 L-1 using 2 m diameter round pond with biofloc media; feeding twice a day and the amount of feed given was 2.5% of total weight, for 158 days. Research parameters included; daily growth rate (%/day), feed efficiency. FCR, weight gain (gr) and length gain (cm), water quality and biofloc content (ml/L). The results showed that the results of the anova test showed a significance value (Sig.) of 0.000 0.05, so there was a significant difference between treatments of the daily growth rate (SGR) parameter, the results of the area test also showed differences between treatments. The highest daily growth rate was obtained in climbing perch, followed by pangas, giant gouramy and Snakehead. The results of the anova test for weight gain showed a significance value (Sig.) of 0.000 0.05, so there was a significant difference between treatments. The anova test results showed a significance value (Sig.) of 0.052 0.005, so there was no significant difference between treatments; the growth of each treatment showed peculiarities between species depending on genes. Anova test results show that the feed conversion of fish research significance value 0.000 0.05 means that the four types of fish studied, significantly different from those reared in the biofloc system Survival rate of fish research significance value 0.000 0.05 means that the four types of fish studied, significantly different from those reared in the biofloc system. Water quality with 4 main parameters is able to support the growth and development of the 4 economically important fish species studied.